Meningkatkan Literasi Siswa Terhadap Pembelajaran PAI di SMP Negeri 3 Cikarang Utara dengan Menggunakan Metode Jigsaw - Alifiah Nursifa; Malika Nur Oktaviani; Muhammad Fadli Mubarok; Nur Aini Farida; M.Makbul (Najah Bestari, 2024)
The aim of this research is to increase students' literacy in Islamic Religious Education (PAI) Learning at SMP Negeri 3 Cikarang Utara through the application of the jigsaw method. This method involves dividing students into small groups to study the material in depth and then sharing the knowledge with the rest of the group. Research was conducted by involving students in learning activities involving group discussions, presentations, and field assessments (observations) by researchers during learning. The research results showed a significant increase in students' literacy towards PAI material, measured through conceptual understanding, analytical skills and problem solving. The implication of this research is that the jigsaw method is effective in increasing student literacy in the context of PAI learning in junior high schools